A geopolymer alkali activator based on red mud raw material and a preparation method thereof

By using sodium chloride and wood ash to dissolve red mud to prepare geopolymer alkali activators and combining them with steel slag powder to fix heavy metals, the problems of high cost and environmental pollution of traditional alkali activators are solved, achieving low-cost and environmentally friendly preparation of alkali activators and performance improvement of geopolymer materials.

CN121063852BActive Publication Date: 2026-02-03HUNAN UNIV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511600061.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-11-04
Publication Date
2026-02-03
Estimated Expiration
2045-11-04

AI Technical Summary

Technical Problem

In existing technologies, traditional alkali activators rely on highly alkaline chemicals such as sodium hydroxide or potassium hydroxide, which are costly and cause serious environmental pollution problems, making it difficult to achieve low-cost and environmentally friendly preparation of alkali activators.

Method used

Sodium chloride and wood ash were used to dissolve alkaline substances in red mud, and steel slag powder was used to fix heavy metals. By controlling the pH value and heavy metal concentration, a geopolymer alkaline activator was prepared, reducing the dependence on traditional high-alkaline chemicals.

Benefits of technology

This enables the preparation of low-cost, environmentally friendly alkali activators, reduces production equipment requirements, decreases carbon emissions and heavy metal pollution, and improves the early strength and long-term durability of geopolymer gel materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121063852B_ABST
    Figure CN121063852B_ABST
Patent Text Reader

Abstract

The application provides a kind of based on red mud raw material geopolymer alkali activator and its preparation method, belongs to geopolymer material technical field.The method of the application includes the following steps: under the condition of stirring and heating, red mud and wood ash are gradually added into sodium chloride solution to form a mixed solution, the mass ratio of red mud and wood ash is (3-6):1, and the solid-liquid mass ratio of red mud and sodium chloride solution is 1:(3-6);the pH value and Na2O release amount of the system are continuously detected, when the pH value of the system is greater than or equal to 12.0 and the change amount within 30 minutes is less than 0.1, steel slag powder is added, the addition amount is 1-5% of the total mass of the mixed solution, and stirring is continued for 20-60 minutes;when the pH value of the system is stable and no longer increases within 2 hours or the Na2O release amount reaches equilibrium, solid-liquid separation is carried out, and the obtained filtrate is the geopolymer alkali activator.The application can reduce the dependence on traditional high-alkaline chemicals and provide a new way for the resource utilization of red mud.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of geopolymer materials technology, specifically relating to a geopolymer alkali activator based on red mud raw material and its preparation method. Background Technology

[0002] Red mud is a waste product generated during the extraction of bauxite. Its main components include sodium hydroxide, potassium hydroxide, bauxite residue, iron minerals, and small amounts of other minerals. Due to its large-scale accumulation and the difficulty of its treatment, red mud is considered an environmental pollution problem. However, the alkaline substances (such as sodium hydroxide and potassium hydroxide) abundant in red mud possess certain chemical reactivity, and these alkaline substances offer potential resource value for the preparation of high-performance materials.

[0003] Geopolymers, as a novel type of cementitious material, possess good environmental adaptability, excellent mechanical properties, and low carbon emissions. Their preparation requires the use of alkaline activators to activate mineral raw materials (such as slag and fly ash), promoting hydration reactions and forming a gel structure with good strength. However, traditional alkaline activators mainly rely on highly alkaline chemicals such as sodium hydroxide or potassium hydroxide, which are costly and increasingly pose environmental pollution problems.

[0004] Therefore, developing a low-cost, environmentally friendly, and efficient alkali activator has become a key direction in current geopolymer research. Summary of the Invention

[0005] This invention provides a geopolymer alkali activator based on red mud raw materials and its preparation method. The geopolymer alkali activator is prepared by dissolving alkaline substances in red mud with sodium chloride and wood ash, which can reduce the dependence on traditional high-alkaline chemical substances and thus effectively solve at least one of the technical problems involved in the background art.

[0006] To solve the above-mentioned technical problems, the present invention is implemented as follows:

[0007] A method for preparing a geopolymer base activator based on red mud raw material includes the following steps:

[0008] Step S1: Prepare a sodium chloride solution with a concentration of 0.5-2.0 mol / L. Under stirring and heating conditions, gradually add red mud and wood ash to the sodium chloride solution to form a mixture. The mass ratio of red mud to wood ash is (3-6):1, and the solid-liquid mass ratio of red mud to sodium chloride solution is 1:(3-6).

[0009] Step S2: Continuously monitor the pH value and Na2O release of the system. When the pH value of the system is ≥12.0 and the change is less than 0.1 within 30 minutes, it is considered that the red mud has been initially dissolved. Under this condition, steel slag powder is added at a rate of 1-5% of the total mass of the mixture, and stirring is continued for 20-60 minutes.

[0010] Step S3: When the pH value of the system stabilizes and no longer increases within 2 hours or the release of Na2O reaches equilibrium, it is considered that the red mud has been completely dissolved. Then, solid-liquid separation is carried out, and the resulting filtrate is the geopolymer alkali activator.

[0011] As a preferred improvement, in step S1, the stirring rate is 100-300 rpm and the heating temperature is 40-80℃.

[0012] As a preferred improvement, in step S3, the solid-liquid separation method is vacuum filtration or pressure filtration.

[0013] As a preferred improvement, the red mud contains ≥35% Fe2O3 and ≥6% Na2O by mass.

[0014] As a preferred improvement, the red mud has a Pb content ≤20mg / kg and a Cd content ≤0.5mg / kg.

[0015] As a preferred improvement, the red mud has a moisture content of 12-15% and a particle size satisfying: d 50 <100µm, d 90 <200µm.

[0016] As a preferred improvement, the wood ash needs to be pretreated before being added. The pretreatment process is as follows:

[0017] The wood ash was heated at 120℃ with a hot air flow rate of 1500 m³ / h. 3 The particles are dried in a hot air furnace for 2 hours, then quickly transferred to a double cone vacuum cooler to cool to below 40°C. After being separated by cyclone separation and dust removal by pulse bag filter, they are sized through a 100µm sieve and finally put into a stainless steel dry ash silo for later use. The stainless steel dry ash silo is slowly pressurized with 0.01MPa dry nitrogen gas.

[0018] As a preferred improvement, the specific surface area of ​​the steel slag powder is ≥400m². 2 / kg; the CaO content in the steel slag powder is ≥4wt%.

[0019] As a preferred improvement, if the pH value of the system is <12.5 or the Pb content is >0.05 mg / L or the Cd content is >0.005 mg / L, add 0.5 wt% steel slag to the mixture, raise the temperature by 2°C and extend the stirring time by 30 min.

[0020] A geopolymer alkali activator based on red mud raw material is prepared by the above-mentioned preparation method of geopolymer alkali activator based on red mud raw material.

[0021] The beneficial effects of this invention are as follows:

[0022] (1) By converting alkaline red mud into a high-value-added alkaline activator through sodium chloride and wood ash, it can be well applied to the preparation of geopolymer gel materials, thereby reducing the dependence on traditional high-alkaline chemicals, reducing the demand for purchasing high-alkaline chemicals, and reducing carbon emissions and costs.

[0023] (2) By solidifying heavy metal ions such as lead and cadmium in red mud with steel slag powder, the residue was rendered harmless.

[0024] (3) The preparation process is simple. The red mud dissolution, alkali activator preparation and heavy metal fixation are completed simultaneously in a single stirred reaction tank, which can greatly reduce the requirements for production equipment and thus reduce production costs. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort, wherein:

[0026] Figure 1 The image shows the XRD pattern of the slag-fly ash-based polymer in Example 1.

[0027] Figure 2 This shows a SEM image of the slag-fly ash macropolymer in Example 1 at a scale of 100 µm.

[0028] Figure 3 The image shows a SEM image of the slag-fly ash macropolymer in Example 1 at a scale of 40µm. Detailed Implementation

[0029] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0030] This embodiment provides a method for preparing a geopolymer alkali activator based on red mud raw material, comprising the following steps:

[0031] Step S1: Prepare a sodium chloride solution with a concentration of 0.5-2.0 mol / L. Under stirring and heating conditions, gradually add red mud and wood ash to the sodium chloride solution to form a mixture. The mass ratio of red mud to wood ash is (3-6):1, and the solid-liquid mass ratio of red mud to sodium chloride solution is 1:(3-6).

[0032] Step S2: Continuously monitor the pH value of the system. When the pH value of the system is ≥12.0 and the change is less than 0.1 within 30 minutes, it is considered that the red mud has been initially dissolved. Under this condition, add steel slag powder at a rate of 1-5% of the total mass of the mixture and continue stirring for 20-60 minutes.

[0033] Step S3: When the pH value of the system stabilizes and no longer increases within 2 hours or the release of Na2O reaches equilibrium, it is considered that the red mud has been completely dissolved. Then, solid-liquid separation is carried out, and the resulting filtrate is the geopolymer alkali activator.

[0034] This invention selects red mud from the alumina production process as the main raw material, supplemented by industrial sodium chloride, wood ash, and steel slag powder as auxiliary materials. The red mud is coarsely crushed and ball-milled to achieve a particle size suitable for the dissolution reaction, thereby increasing the specific surface area and improving the dissolution efficiency of alkaline components. The wood ash is dried and sieved, and if necessary, can be further ground to a fineness matching that of the red mud particles.

[0035] During the reaction, if the pH value of the system is <12.5 or the Pb content is >0.05mg / L or the Cd content is >0.005mg / L, add 0.5wt% steel slag to the mixture, raise the temperature by 2℃ and extend the stirring time by 30min.

[0036] Sodium chloride solution provides sodium ions (Na+) + It plays a crucial role in the dissolution process. Its main principles include the following aspects:

[0037] (1) Ion enhancement effect

[0038] Ionic strength of sodium chloride solution: Sodium chloride solution provides a large amount of Na+. + and Cl - When sodium chloride solution comes into contact with red mud, sodium ions in the solution enhance the solubility of sodium, potassium, and other metal salts in the red mud through an ion-enhancing effect.

[0039] (2) Ion exchange

[0040] Red mud typically contains various minerals (such as bauxite and iron ore), which react with Na... + and K + Alkaline substances combine to form mineral salts. Sodium chloride solution contains Na... +It can undergo ion exchange reactions with some metal ions in red mud, replacing these metal ions from the minerals and thus promoting their dissolution.

[0041] (3) Dissolve sodium hydroxide and carbonate

[0042] Red mud contains a certain amount of NaOH, KOH, and carbonates (such as Na2CO3). These substances can dissolve further in the presence of sodium chloride solution, thereby releasing more sodium ions.

[0043] Wood ash is the ash obtained from burning plants and mainly contains alkaline substances such as KOH and Na₂CO₃. The principle by which wood ash dissolves the alkaline substances in red mud includes the following aspects:

[0044] (1) Provide K +

[0045] KOH in wood ash is one of the key components for dissolving alkaline substances in red mud. KOH dissociates into K+ in water. + and OH - K + It can react with the minerals in red mud, helping to dissolve alkaline components such as sodium and potassium.

[0046] (2) Provide Na2CO3

[0047] Na2CO3 can react with metal ions (such as sodium and potassium) in red mud to form soluble carbonates, which further promotes the dissolution of alkaline substances in red mud.

[0048] (3) Synergistic effect of increasing solubility

[0049] The KOH and Na2CO3 in wood ash work together to provide a strong alkaline environment. This enhanced alkalinity helps convert insoluble substances in red mud into readily soluble ones, thus improving the dissolution efficiency of alkaline components.

[0050] When sodium chloride and wood ash are used together, they work synergistically through ion exchange and dissolution enhancement mechanisms to promote the dissolution of alkaline substances in red mud.

[0051] (1) Sodium chloride solution

[0052] Sodium chloride solution provides Na + It enhances solubility and undergoes ion exchange reactions with other metal ions in the red mud, dissolving hydroxides and carbonates from the red mud.

[0053] (2) Wood ash

[0054] Wood ash provides K +It works with Na2CO3 to further enhance the dissolution effect, especially when dissolving metal salts such as sodium and potassium, where it has a synergistic effect.

[0055] Ultimately, through the combined action of these two solvents, alkaline substances in the red mud (such as sodium hydroxide, potassium hydroxide, carbonates, etc.) are effectively dissolved, thus providing the necessary alkaline activators for the geopolymer reaction.

[0056] Steel slag powder is used as a calcium source and heavy metal fixative. The active calcium released by the steel slag reacts with lead and cadmium ions in the solution under a highly alkaline environment to form hydroxide or carbonate precipitates, which are further encapsulated by the calcium silicate phase, thereby achieving stable solidification of heavy metals.

[0057] By monitoring the pH value and heavy metal concentration of the system in real time, the addition and stirring time of steel slag can be automatically adjusted as needed to achieve adaptive control.

[0058] In step S1, the stirring rate is 100-300 rpm and the heating temperature is 40-80℃. These stirring and heating conditions promote the reaction and thus accelerate the dissolution of red mud and wood ash.

[0059] In step S3, the solid-liquid separation is performed using vacuum filtration or pressure filtration. The resulting filter residue is washed countercurrently with a small amount of clean water to recover residual solution and reduce surface alkalinity. The washed filter residue can be used as cement raw material or road filler, achieving closed-loop utilization of solid waste and offering the advantage of low heavy metal ion leaching rate. The resulting filtrate can be used directly according to application requirements, or it can be concentrated through vacuum evaporation to increase alkalinity. After cooling, the concentrated liquid is stored in a sealed, inert gas-protected tank to prevent carbon dioxide absorption and subsequent alkalinity decrease. During storage, periodic stirring or circulation ensures uniform composition of the stored liquid.

[0060] This embodiment also provides a geopolymer alkali activator based on red mud raw material, which is prepared by the above-described preparation method of the geopolymer alkali activator based on red mud raw material.

[0061] The activator prepared by this invention can be directly used as an alkali activator in the compounding process of geopolymer cementitious materials. The resulting geopolymer cementitious materials have the advantages of high early strength, low heavy metal leaching, and good long-term durability.

[0062] The preparation method provided by this invention can be well applied to industrial production. It can simultaneously complete the dissolution of red mud, the preparation of alkali activators and the fixation of heavy metals in a single stirred reaction tank, which can greatly reduce the requirements for production equipment and thus reduce production costs.

[0063] After the red mud enters the factory, it needs to undergo a detailed three-level inspection:

[0064] The first-level inspection uses a portable X-ray fluorescence spectrometer (handheld, 30kV, 10µA) to quickly scan the bulk red mud and remove abnormal batches with Fe2O3 mass percentage <35wt% or Na2O mass percentage <6wt%.

[0065] The second level of testing involves cross-calibrating the contents of SiO2, Al2O3, Na2O, CaO, Fe2O3, and heavy metals (Pb, Cd, Cr, As) in the laboratory using XRF, ICP-OES, and wet chemical titration to ensure that the Pb content is ≤20mg / kg and the Cd content is ≤0.5mg / kg.

[0066] The third-level inspection confirmed that the particle size of the red mud met the following requirement using a laser particle size analyzer: d 50 <100µm, d 90 <200µm, to avoid excessive load on subsequent ball milling.

[0067] After passing three levels of testing, the red mud is first dehydrated to a moisture content of 12-15% in a belt vacuum filter (1m×30m, vacuum -80kPa), and then transported into a fully enclosed steel silo (conical bottom design, moisture-proof and nitrogen-filled, with a nitrogen replacement rate of 2m / s under normal pressure) within 1 hour. 3 / h) Zoned stacking. Online temperature and humidity meters and CO2 monitors are installed inside the steel silos. A 5000m³ / h valve automatically activates when the relative humidity (RH) > 60% or the CO2 content > 0.3 vol%. 3 / h dehumidification air conditioner and fan circulation.

[0068] Sodium chloride needs to undergo two-stage packaging in the packaging workshop (inner polyethylene bag, outer woven bag), and be stacked on a moisture-proof pallet 15cm from the ground and 30cm from the wall, with a stacking height of ≤1.6m; moisture content is randomly sampled every 24 hours, and if the clumping rate is found to be >3%, it is immediately reworked, broken, and repackaged.

[0069] The wood ash needs to be pretreated before being added. The pretreatment process is as follows:

[0070] The wood ash was heated at 120℃ with a hot air flow rate of 1500 m³ / h. 3 The particles are dried in a hot air furnace for 2 hours, then quickly transferred to a double cone vacuum cooler to cool to below 40°C. After dust removal by cyclone separation and pulse bag filter, they are granulated through a 100µm sieve and fed into a 5m³ filtration system. 3 The stainless steel dry ash silo is slowly pressurized with 0.01MPa dry nitrogen gas for positive pressure protection.

[0071] Steel slag powder is obtained by ball milling and high-efficiency powder selection of blast furnace slag, with a specific surface area of ​​≥400m² as monitored in real time (BET method). 2 / kg, CaO content ≥4wt%, and stored in sealed ton bags in a cool, ventilated place. Prolonged contact with humid air is strictly prohibited to prevent autohydration and clumping.

[0072] After entering the crushing section, the red mud is first coarsely crushed to a particle size <5mm by a PE-600×900 jaw crusher, and then a closed-circuit grinding system is formed by an MQY-2436 wet grate ball mill and a high-frequency vibrating screen (75µm screen). The ball mill is equipped with 15t of high-chromium steel sections, with a filling rate of 40%, a slurry consistency of 70wt%, and a circulating load of 250%. The feed rate is adjusted to 15t / h by an automatic feeding screw pump to ensure that the particle size of the final product meets the following requirements: d 50 ≈75µm, d 90 ≤120µm. The slurry from the mill is then transferred to a 30wt% flowing slurry tank for temporary storage after being filtered by plate and frame filter press.

[0073] The wood ash is granulated twice using a CMF-750 ultrafine airflow mill and then mixed with red mud at a 1:1 batch ratio to ensure that the subsequent mixing error is <±0.5%. The entire process employs a four-stage dust removal system: a coarse-particle bag filter (8000 m³ / h). 3 / h) → Ball mill dust collector (air volume 12000m³ / h) 3 / h) → Finished product screen pulse bag filter (air volume 4000m) 3 / h) → Central dust collection in negative pressure pipeline network (air volume 15000m³) 3 / h), dust emission <20mg / m³ 3 All recycled dust is returned to the process, and no secondary waste is generated.

[0074] The following detailed description of the geopolymer alkali activator based on red mud raw materials provided by the present invention is based on specific embodiments.

[0075] Example 1

[0076] This embodiment provides a method for preparing a geopolymer alkali activator based on red mud raw materials, including the following steps:

[0077] With an effective volume of 6m 3 A 4m³ volume of water was poured into a 304L stainless steel melting tank containing a K-type steam jacket and stirring blades. 3 Deionized water was used, and 235 kg of NaCl was added quantitatively using a screw metering pump. The steam jacket and stirring blades were turned on. The temperature of the steam jacket was 45℃, and the speed of the stirring blades was 150 rpm. The mixture was stirred continuously for 20 minutes to obtain a NaCl solution with a concentration of 1 mol / L.

[0078] Prepare a 600L suspension of 20wt% wood ash in an eccentrically agitated reactor; the K2O and soluble CaCO3 in the wood ash will provide CO3 in the subsequent reaction. 2- K + Promote the growth of Na in red mud + Migration and chemical displacement.

[0079] The screw conveyor is controlled to pump red mud slurry into the dissolving tank at a constant speed of 100 kg / min. The system maintains the solid-liquid mass ratio of the slurry at 1:4 and the solid content at 20 wt% through a PID algorithm. After 15 minutes of mud addition, 50 kg of steel slag powder is slowly added at a rate of 10 kg / min to avoid local pH fluctuations.

[0080] The dissolution tank is equipped with a pH / ORP electrode and an online ICP-OES bypass sampling device, which automatically detects Pb every 30 minutes. 2+ Cd 2+ Equal concentration with Na + Release rate and upload to DCS. If pH < 12.5 or Pb > 0.05 mg / L or Cd > 0.005 mg / L, the system triggers "calcium supplementation" mode: add 0.5 wt% steel slag to the mixture, raise the temperature by 2°C and extend the stirring time by 30 min.

[0081] During the solid-liquid separation stage, the reaction slurry is pumped to a 2.5m×30m vacuum belt filter, with a filter cloth of 750g / m² polypropylene. 2 Vacuum -80 kPa, target filter cake moisture content ≈ 30%. Based on a permeability coefficient of 1.5 × 10⁻⁶... -11 m 2 Based on a compression index of 0.85, the optimal filtration rate is calculated to be 3.2 kg / m³. 2 The filtration zone employs a three-stage air extraction system: main filtration → 0.3m 3 Deionized water backwashing → air extraction dehydration; then the filter cake is turned into a screw conveyor and sprayed with 0.2m. 3 Water was rapidly dehydrated to reduce the Pb / Cd conductivity to <5 mS / cm. All filtrate was recovered, and the fine residue was centrifuged in a horizontal screw centrifuge and refluxed back to the front stage. After 24 hours of aging, the filter cake was measured using the TCLP (Toxicity Leaching Method): Pb leaching was 2.7 mg / L and Cd leaching was 0.25 mg / L, meeting the criteria for non-hazardous solid waste and suitable for co-processing in cement kilns at a rate of 15 wt%.

[0082] During the concentration stage, the filtrate with a solid content of 7wt% is fed into an SSF-20 L membrane evaporator. The evaporator temperature is 60℃, the jacket steam pressure is 0.15MPa, the vacuum degree is 0.08MPa, and the evaporation ratio is 3kg / h. Triple-effect flash evaporation recovers heat energy, with an overall efficiency of 85%. 0.05wt% polyaspartic acid scale inhibitor is added at the inlet, and the evaporator is cleaned every 48 hours using reverse steam and 2wt% citric acid circulation. After concentration to a solid content of 15wt%, the filtrate is cooled to 35℃ via a plate heat exchanger and then pumped into a 20m³ / h container. 3 Vertical storage tank (FEP lining, design pressure 0.35MPa). The tank top is nitrogen-sealed at 0.02MPa and equipped with a flame arrester. Liquid level, temperature and pH are monitored online. Monthly sampling is performed for pH 13.1±0.1 and Na2O 80±3g / L. If the threshold is exceeded, the system will automatically circulate and mix for 30 minutes.

[0083] The workshop floor is coated with a 3mm epoxy anti-corrosion layer, and is resistant to 48h NaOH immersion. Installation range: 10,000m². 3 The roof exhaust gas, with a capacity of / h, is discharged after passing through a two-stage Venturi scrubber. The scrubbing solutions are 2wt% NaOH and 2wt% HCl, respectively, with NaOH / HCl aerosol concentration <10mg / m³. 3 Accident pool 200m 3 It can accommodate the largest single tank leak and automatically neutralizes within 5 minutes of Ca(OH)2 dry powder injection. Wastewater is carbonized with CO2 to pH 9.0, then adjusted to pH 8.0±0.2 with 5wt% lime slurry; sediment is filtered and reused; the supernatant meets GB8978 Class I discharge standards. The entire plant is monitored 24 / 7 online for VOCs, particulate matter, pH, Pb, and Cd, connected to the ecological and environmental protection bureau, with SMS alerts for exceeding standards. Work requires N95 and alkali-resistant protective gear; disinfection is performed every shift, and the dosage is recorded.

[0084] The finished alkaline solution has a low modulus (SiO2 / Na2O≈0.5), which needs to be adjusted to 1.0-1.2 using water glass or nano-silica sol to produce a high-strength geopolymer. The recommended formula is as follows: 60 parts by weight of slag, 40 parts by weight of fly ash, 6-8 parts by weight of the activator provided in this invention, water-binder ratio of 0.30-0.35, initial flowability of 170±10mm; compressive strength ≥40MPa after 24h steam curing at 60℃, room temperature strength of 50-55MPa after 28d curing, and splitting tensile strength of 5.5MPa. Observe the XRD pattern and microstructure diagram of the geopolymer, such as... Figure 1 As shown, XRD reveals that C-(A)-SH and (N,K)-ASH are the main products in the geopolymer; Figure 2 and Figure 3 As shown, SEM confirmed that Pb / Cd is encapsulated within calcium silicate gel or carbonate crystals, with an atomic percentage of <0.03%. After 90 days of durable immersion in EN12457-2, TCLP1311, and NEN7375-DT, the Pb leaching amount was <10µg / L, and the Cd leaching amount was <2µg / L; the mass loss after 30 cycles of sulfate wet and dry treatment was <1.5%. Life cycle assessment showed that compared to the traditional composite system of NaOH and water glass, each ton of cementitious material reduced CO2 emissions by 260kg CO2eq, and the cost of purchased alkali decreased by approximately 35%.

[0085] Example 2

[0086] In a 304L stainless steel melting tank (effective volume 6m³) 3 ) was injected into 4m 3 Deionized water was used, and 117 kg of NaCl was added to prepare a 0.5 mol / L sodium chloride solution. The solution was heated to 40°C and stirred at 100 rpm with a paddle. Then, red mud and wood ash were gradually added at a mass ratio of 5:1, maintaining a solid-liquid mass ratio of 1:6 and a solid content of approximately 14 wt%.

[0087] After 20 minutes of feeding, when the pH of the solution rises to 12.0 and remains stable for 20 minutes, add 30 kg of steel slag powder (about 1 wt%) and continue stirring for 20 minutes.

[0088] The dissolution reaction was considered complete when the pH no longer increased within 2 hours. The slurry was pumped into a vacuum belt filter (vacuum -70 kPa), with a filter cake moisture content of approximately 35%. The filtrate contained approximately 55 g / L of Na₂O and had a pH of 12.8. It was subsequently concentrated to a solid content of 12 wt% by evaporation at 50°C and then cooled for storage.

[0089] The resulting filtrate was used to prepare geopolymer cementitious materials in a slag / fly ash system. The compressive strength at room temperature for 28 days was approximately 42 MPa, and the leaching amounts of heavy metals Pb and Cd were less than 0.02 mg / L and 0.002 mg / L, respectively.

[0090] Example 3

[0091] In a 304L stainless steel melting tank (effective volume 6m³) 3 ) was injected into 4m 3 Deionized water was mixed with 468 kg of NaCl to prepare a 2 mol / L sodium chloride solution. The solution was heated to 80°C and stirred at 300 rpm. Then, red mud and wood ash were gradually added at a mass ratio of 3:1, maintaining a solid-liquid mass ratio of 1:3 and a solid content of approximately 25 wt%. After 10 minutes of addition, the solution pH rose to 13.0 and remained stable for 30 minutes. At this point, 100 kg of steel slag powder (approximately 5 wt%) was added, and stirring continued for another 60 minutes.

[0092] The reaction was complete when online monitoring showed that the Na₂O release rate no longer increased. The slurry was pumped into a vacuum belt filter (vacuum -85 kPa), with a filter cake moisture content of approximately 28%. The Na₂O concentration in the filtrate was approximately 90 g / L, and the pH was 13.2. The filtrate was concentrated to 18 wt% solids by evaporation at 65°C and then cooled for storage.

[0093] The obtained filtrate was used to prepare geopolymer cementitious materials in a slag / fly ash system. The compressive strength was about 48 MPa after steam curing at 60℃ for 24 h, and the room temperature strength was 58 MPa after 28 days. The heavy metal leaching amounts of Pb and Cd were less than 0.01 mg / L and 0.001 mg / L, respectively.

[0094] The main mechanisms involved in the above embodiments are as follows:

[0095] (1) Na + Displacement and release;

[0096] (2) Ca(OH)2 and Pb 2+ / Cd 2+ The insoluble Pb(OH)2 and Cd(OH)2 are generated, which are then converted into PbCO3 and CdCO3.

[0097] (3) Calcium silicate gel encapsulates heavy metals. After 3 hours, approximately 25 kg / t of Na2O is dissolved, the filtrate contains 70-75 g / L of Na2O, and the Pb / Cd removal rate is ≥97.5%.

[0098] The process design in this embodiment fully considers environmental and safety requirements. The workshop operates under negative pressure, and exhaust gas is discharged after passing through an alkaline scrubbing tower or a two-stage acid-alkali scrubbing process. An emergency pool is installed on the workshop floor to collect and neutralize any leaked liquids. Process wastewater is discharged in compliance with standards after carbonization and neutralization, and dust and residue are utilized as resources. Key indicators are monitored online and connected to the environmental protection system to achieve full process control.

[0099] The embodiments of the present invention have been described above with reference to the accompanying drawings. However, the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of the present invention without departing from the spirit and scope of the claims, and all of these forms are within the protection scope of the present invention.

Claims

1. A method for preparing a geopolymer alkali activator based on red mud raw material, characterized in that, Includes the following steps: Step S1: Prepare a sodium chloride solution with a concentration of 0.5-2.0 mol / L. Under stirring and heating conditions, gradually add red mud and wood ash to the sodium chloride solution to form a mixture. The mass ratio of red mud to wood ash is (3-6):1, and the solid-liquid mass ratio of red mud to sodium chloride solution is 1:(3-6). Step S2: Continuously monitor the pH value and Na2O release of the system. When the pH value of the system is ≥12.0 and the change is less than 0.1 within 30 minutes, it is considered that the red mud has been initially dissolved. Under this condition, steel slag powder is added at a rate of 1-5% of the total mass of the mixture, and stirring is continued for 20-60 minutes. Step S3: When the pH value of the system stabilizes and no longer increases within 2 hours or the release of Na2O reaches equilibrium, it is considered that the red mud has been completely dissolved. Then, solid-liquid separation is carried out, and the resulting filtrate is the geopolymer alkali activator.

2. The method for preparing the geopolymer alkali activator based on red mud raw material according to claim 1, characterized in that, In step S1, the stirring speed is 100-300 rpm and the heating temperature is 40-80℃.

3. The method for preparing the geopolymer alkali activator based on red mud raw material according to claim 1, characterized in that, In step S3, the solid-liquid separation method is vacuum filtration or pressure filtration.

4. The method for preparing the geopolymer alkali activator based on red mud raw material according to claim 1, characterized in that, The red mud contains ≥35% Fe2O3 and ≥6% Na2O by mass.

5. The method for preparing the geopolymer alkali activator based on red mud raw material according to claim 1, characterized in that, The red mud has a Pb content ≤20mg / kg and a Cd content ≤0.5mg / kg.

6. The method for preparing the geopolymer alkali activator based on red mud raw material according to claim 1, characterized in that, The red mud has a moisture content of 12-15% and a particle size that meets the following requirement: d 50 <100µm, d 90 <200µm.

7. The method for preparing the geopolymer alkali activator based on red mud raw material according to claim 1, characterized in that, The wood ash needs to be pretreated before being added. The pretreatment process is as follows: The wood ash was heated at 120℃ with a hot air flow rate of 1500 m³ / h. 3 The particles are dried in a hot air furnace for 2 hours, then quickly transferred to a double cone vacuum cooler to cool to below 40°C. After being separated by cyclone separation and dust removal by pulse bag filter, they are sized through a 100µm sieve and finally put into a stainless steel dry ash silo for later use. The stainless steel dry ash silo is slowly pressurized with 0.01MPa dry nitrogen gas.

8. The method for preparing the geopolymer alkali activator based on red mud raw material according to claim 1, characterized in that, The specific surface area of ​​the steel slag powder is ≥400m². 2 / kg; the CaO content in the steel slag powder is ≥4wt%.

9. The method for preparing the geopolymer alkali activator based on red mud raw material according to claim 1, characterized in that, If the pH value of the system is <12.5 or the Pb content is >0.05 mg / L or the Cd content is >0.005 mg / L, add 0.5 wt% steel slag to the mixture, raise the temperature by 2°C and extend the stirring time by 30 min.

10. A geopolymer alkali activator based on red mud raw material, characterized in that, It is prepared by the method of preparing geopolymer alkali activator based on red mud raw material as described in any one of claims 1-9.

Citation Information

Patent Citations

  • Full-industrial solid waste filling material for large-cavity goaf and preparation method of full-industrial solid waste filling material

    CN112707690A

  • Geopolymer curing material based on fly ash and red mud and preparation method of geopolymer curing material

    CN113735515A